2007
DOI: 10.1121/1.2799482
|View full text |Cite
|
Sign up to set email alerts
|

Detection and discrimination of simple and complex sounds by hearing-impaired Belgian Waterslager canaries

Abstract: Dooling, R. J.; Leek, M.R., Leek, M.R.; and Poling, K., "Detection and discrimination of simple and complex sounds by hearing-impaired Belgian Waterslager canaries" (2007). Journal of the Acoustical Society of America, 122, 6,[3615][3616][3617][3618][3619][3620][3621][3622][3623][3624][3625][3626][3627] Belgian Waterslager canaries ͑BWC͒ are bred to produce a distinctive low-pitched song with energy restricted to a lower range of frequencies than in other types of canaries. Previous studies have shown a high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
1
15
1
Order By: Relevance
“…Changes in the shape of the auditory filters may result in reduced ability to “hear out” high frequency sounds that occur in complex acoustic environments. The reduced frequency selectivity shown here may be related to the reduced frequency discrimination ability and changes in temporal resolution previously shown in BWC (Lauer et al 2007). On the other hand, good frequency resolution at low frequencies coupled with poor frequency resolution at high frequencies may support learning of the low-pitched vocalizations characteristic of the BWC strain.…”
Section: Discussionmentioning
confidence: 56%
“…Changes in the shape of the auditory filters may result in reduced ability to “hear out” high frequency sounds that occur in complex acoustic environments. The reduced frequency selectivity shown here may be related to the reduced frequency discrimination ability and changes in temporal resolution previously shown in BWC (Lauer et al 2007). On the other hand, good frequency resolution at low frequencies coupled with poor frequency resolution at high frequencies may support learning of the low-pitched vocalizations characteristic of the BWC strain.…”
Section: Discussionmentioning
confidence: 56%
“…Previous anatomical and behavioral studies showed pathologies in BW canaries as young as 2 months (Gleich et al, 1994a; Lauer, 2006; Lauer et al, 2009; Lauer et al, 2007; Okanoya and Dooling, 1987; Okanoya et al, 1990). However, it was not clear whether the pathologies observed in the young adult birds are congenital or progress during post-hatch development.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, this strain of canary has an auditory threshold shift of 20–40 dB at frequencies above 1 kHz (Okanoya and Dooling, 1985; 1987), exhibits poor frequency discrimination above 1 kHz and has reduced temporal integration (Lauer et al, 2007). However, they are better on some temporal discrimination tasks than non-BW canaries (e.g., gap detection and temporally reversed stimuli; Lauer et al, 2007). Cross-breeding experiments have confirmed a hereditary basis for this hearing loss (Okanoya et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Cochlear-implant users can discriminate the +SCHR and -SCHR at better than chance performance for F0s of 400 Hz and less, but they did not perform as well as NH subjects (Drennan et al, 2008). Discrimination of +SCHR and −SCHR has not been tested in HI non-cochlear implant listeners; however, HI canaries have been shown to perform slightly better than NH canaries when discriminating between +SCHR and −SCHR (Lauer et al 2007). The difference in discrimination ability in NH and HI canaries was attributed to differences in frequency selectivity, in that broader filters in damaged ears may support better resolution of temporal characteristics of sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated differences in the masking effectiveness of positive-(+SCHR) and negative-phase (−SCHR) versions of Schroeder harmonic complexes in normal-hearing (NH) and hearingimpaired (HI) listeners (Carlyon and Datta 1997;Kohlrausch and Sander 1995;Lauer et al 2006;Leek et al 2000;Lentz and Leek 2001;Dau 2001, 2004;Smith et al 1986;Summers and Leek 1998). These complexes have similar envelopes and long-term frequency spectra but reversed withinperiod temporal structure.…”
Section: Introductionmentioning
confidence: 99%